2014
DOI: 10.23986/afsci.41471
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of suppression of Pythium wilt of cucumber by compost

Abstract: There is increasing global interest in using compost to suppress soil-borne fungal and bacterial diseases and nematodes. We studied the reproducibility of compost suppressive capacity (SC) against Pythium wilt of cucumber using nine composts produced by the same composting plant in 2008 and 2009. A bioassay was set up in a greenhouse using cucumber inoculated with two strains of Pythium. The composts were used as 20% mixtures (v:v) of a basic steam-sterilized light Sphagnum peat and sand (3:1, v:v). Shoot heig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Also some other studies demonstrated such a general suppressive effect of compost against Pythium spp. when amended to peat-like growing media (Pane et al 2011;Alfano et al 2011;Vestberg et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Also some other studies demonstrated such a general suppressive effect of compost against Pythium spp. when amended to peat-like growing media (Pane et al 2011;Alfano et al 2011;Vestberg et al 2014).…”
Section: Discussionmentioning
confidence: 99%